Some properties of intuitionistic fuzzy modules - Behnam Talaee; Mehrnoosh Sobhani; Bijan Davvaz (Journal of Fuzzy Extension and Applications)
In this paper, we discuss the structure of intuitionistic fuzzy modules and investigate some fundamental properties of them. Also we study about intuitionistic fuzzy homomorphisms between intuitionistic fuzzy modules.We study about exact sequences, products and co-products, func- tors and relating topics in IFR−Mod and investigate the relationship between them, where IFR−Mod is category whose objects are intu- itionidtic fuzzy modules and morphisms are intuitionistic fuzzy homo-morphisms.For a commutative ring R and two intuitionistic  fuzzy R-modules A=(µA, νA) ≤IF M, B = (µB,  νB) ≤IF N,  we show that  (A, B) = (α, β) is an intuitionistic fuzzy R-module.